2017
DOI: 10.1002/dac.3312
|View full text |Cite|
|
Sign up to set email alerts
|

Search me if you can: Multiple mix zones with location privacy protection for mapping services

Abstract: The mobile vehicle is gaining popularity nowadays using map services like Google Maps and other mapping services. However, map services users have to expose sensitive information like geographic locations (GPS coordinates) or address to personal privacy concerns as users share their locations and queries to obtain desired services. Existing mix zones location privacy protection methods are most general purposed and theoretical value while not applicable when applied to provide location privacy for map service … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…In an ideal mix zone, it is equiprobable for x to be any of the users in the entering users set V out , having p x → y = 1true∣normalVouttrue∣. However, in real world, the effectiveness of the mix zone is constrained by many factors, such as the number of road segments at the intersections, the probability distribution between the road segments, the mobile users' travel speed constraint inside the mix zone region, etc . The more uniform the probability distribution is, the higher the entropy is and the more difficult the real user can be identified.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an ideal mix zone, it is equiprobable for x to be any of the users in the entering users set V out , having p x → y = 1true∣normalVouttrue∣. However, in real world, the effectiveness of the mix zone is constrained by many factors, such as the number of road segments at the intersections, the probability distribution between the road segments, the mobile users' travel speed constraint inside the mix zone region, etc . The more uniform the probability distribution is, the higher the entropy is and the more difficult the real user can be identified.…”
Section: Resultsmentioning
confidence: 99%
“…Henceforth, it can be concluded that less probable mappings may not efficiently measure anonymity. However, it can be seen that, when mapping probability distribution is uneven, then there might be attacks constructed on probability analysis . Alternatively, we cannot say that road intersections are as better as mix zones just because ASS is larger than K. The set of users inside the anonymity count might become less probable beneath timing and transition attacks and may not efficiently count headed for anonymity.…”
Section: Resultsmentioning
confidence: 99%
“…Many protocols take advantage of routing and time stamp . Routing and time stamps are used to make real‐time decisions about the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Then they proposed the new remote user authentication scheme to overcome the identified weaknesses. In 2017, Memon et al proposed the location privacy protection for mapping services. In the same year, Memon et al also proposed pseudonym changing strategy with multiple mix zones for trajectory privacy protection in road networks.…”
Section: Introductionmentioning
confidence: 99%